Arrhythmia Mechanism on Diabetes Mellitus: A Narrative Review - Ricky Juliardi Mezal; Hauda El Rasyid (HM Publisher, 2022)
Diabetes mellitus is a metabolic disorder characterized by an increase in blood sugar levels. The mechanism of arrhythmias in patients with diabetes mellitus is complex and unique. This is an independent factor in the occurrence of arrhythmias through several slightly different mechanisms in non-diabetics. Hyperglycemia, hypoglycemia, remodeling, autonomic neuropathic dysfunction, fibrosis, and oxidative changes, and metabolic stress play an important role in the occurrence of arrhythmias in diabetes. This narrative review was at least to describe the mechanism of arrhythmia in diabetes mellitus.